Perancangan Sistem Informasi Pengarsipan Surat Pada Kantor Kejaksaan Kabupaten Mamuju Utara - Hasrul; Amriadi; Nur Fadillah Suprayitno (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
Along with the development of technology today is increasingly demanding the importance of information for every organization. One of the sources of informationcan support the process of administrative activities is archiving. Filing not only from organizational activities, but archiving can also received or created from the organization in the context of carrying out activities and kept as evidence of its policies and activities in the implementation of activities every organization. North Mamuju District Prosecutor's Office in carrying out duties and its activities in archiving activities, namely managing incoming and outgoing mail exit is still manual, namely by recording every letter in the book registers and their archives are stored in the filing cabinet provided so that the work process takes a longer time. From activity the work carried out in the management of incoming and outgoing letters, the author trying to provide solutions using information technology, namely: using a mail filing information system so that in work activities, employees will be faster and more efficient. Web-based filing information system developed using the Laravel framework can solve the problem Document archiving manually at the North Mamuju Prosecutor's Office because it has been has features that suit the needs of users. As for the results that It is hoped that with this information system, it will also relieve and accelerate employee performance in archiving incoming and outgoing letters to the North Mamuju District Attorney.